Logistics at Sytel Company - Barua, S. K. (SAGE knowledge. Cases., 2016)
Management decisions require concepts, frameworks, and techniques to be applied from several functions and disciplines simultaneously to find solutions. The case illustrates the application of optimization along with financial evaluation of investment decisions, to a decision on warehousing facing Sytel. The case identifies the elements of cash flows that are relevant for decisions pertaining to the setting up of warehouses. The instructor can make changes in the figures provided in the case to broaden the scope of understanding that can be imparted through the case.